PELAKSANAAN PEMBELAJARAN REMEDIAL UNTUK MENGATASI KESULITAN BELAJAR PADA MATERI PECAHAN SISWA KELAS V SD NEGERI 32 PONTIANAK TENGGARA - Sarastiwy, Nadella; Margiati, K.Y.; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purposed of the study was determined whether remedial learning could overcome learning difficulties of students on the fraction material in V grade SD Negeri 32 South East Pontianak. The research method used was descriptive research with case study. The subject consisted of 23 in V grade. The technique of the data collection used was measurement technique. The data collection used was the form of essays in the form of 10 questions. The learning result of V grade students SD Negeri 32 in South East Pontianak in mathematics lessons, especially fractional material after given a remedial learning was increased from diagnostic tests to remedial 1 or remedial 1 to remedial 2. The percentage of students who complete increased from 39,13% in diagnostic tests became 42,85% on remedial 1 and increased by as much as 75% on remedial 2. This means that the implementation of remedial learning was good applied to overcome student learning difficulties in fraction material. Keywords: Learning, Learning Difficulties, Remedial Math